Option Value: Empirical Evidence From a Case Study of Recreation and Water Quality: Reply - Greenley, Douglas A.; Walsh, Richard G.; Young, Robert A. (Quarterly Journal of Economics, 1985)
Journal Article Option Value: Empirical Evidence from a Case Study of Recreation and Water Quality: Reply Get access Douglas A. Greenley, Douglas A. Greenley Moorhead State University Search for other works by this author on: Oxford Academic Google Scholar Richard G. Walsh, Richard G. Walsh Colorado State University Search for other works by this author on: Oxford Academic Google Scholar Robert A. Young Robert A. Young Colorado State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 100, Issue 1, February 1985, Pages 295–299, https://doi.org/10.2307/1885749 Published: 01 February 1985